Mean velocity and peak systolic velocity can help determine ischaemic and non-ischaemic priapism. Issue 7 (July 2017) - von Stempel, C.; Zacharakis, E.; Allen, C.; Ramachandran, N.; Walkden, M.; Minhas, S.; Muneer, A.; Ralph, D.; Freeman, A.; Kirkham, A.
Abstract : Aim: To determine the threshold waveform characteristics at Doppler ultrasound (DUS) to differentiate between ischaemic and non-ischaemic priapism. Materials and methods: Fifty-two patients were categorised into "ischaemic" and "non-ischaemic" types based on clinical and blood-gas findings: 10 patients with non-ischaemic priapism; 20 with ischaemic priapism before surgical shunt placement and 22 with ischaemic priapism after surgical shunt placement. DUS traces were analysed: peak systolic velocity (PSV) and mean velocity (MV) were calculated. Histological samples were obtained at the time of surgery. Three clinical outcome groups were defined: (1) normal, (2) regular use of pharmacostimulation, and (3) refractory dysfunction/penile implant. Results: All non-ischaemic priapism cases had a PSV >50 cm/s and all but one had an MV of >6.5 cm/s. In pre-surgery ischaemic cases, all men had a PSV <50 cm/s and MV <6.5 cm/s. Two flow patterns were observed in this group: PSV <25 cm/s in all men scanned before needle aspiration; and in 6/14 after needle aspiration, a high velocity/high resistance (low net inflow) pattern, with peak systolic flows >22 cm/s but diastolic reversal. In post-surgery ischaemic priapism, flow parameters overlapped with the non-ischaemic group. PSV/MV did not predict clinical outcome or histology. Conclusion: In the present cohort, PSV <50 cm/s and MV <6.5 cm/s were predictive of ischaemic priapism (pre-shunt; p<0.01). Patients with ischaemic priapism may show PSV >22 cm/s, but have diastolic reversal and therefore low net perfusion. Post-shunt, DUS findings were extremely variable and did not predict histology or clinical outcome. Highlights: A measure of peak systolic velocity, without considering diastolic reversal, may lead to erroneous impression of high flow in ischaemic priapism. All cases of ischaemic priapism before surgical shunt or washout had a mean velocity of 6.5cm/s and a peak systolic velocity of less than 50cm/s. In the post shunt ischaemic penis, Doppler is not a reliable way of predicting clinical outcome.